Management Of Reading Community Pelosok Bumi In Karawang Regency - Anas Muthtar; Hidayat Hidayat; Ahmad Syahid (Universitas Negeri Padang, 2022)
Aims to describe planning, organizing, and supervising reading community. The concept of George Robert Terry (2007:31)